Language planning and education - Ferguson, Gibson (Edinburgh textbooks in applied linguistics., 2006)
Offers a topical introduction to a resurgent academic discipline. This book explores the importance of language in issues of migration, globalisation, cultural diversity, nation-building, education and ethnic identity. It describes the emergence and evolution of language planning as an academic discipline.